Factors Affecting the Preparedness of Pregnant Women Facing COVID-19 Vaccination - Gusti Ayu Dwina Mastryagung; Ni Nyoman Sri Artina Dewi; Ni Putu Indah Putri Diana (Universitas Andalas, 2022)
The COVID-19 disease also affects children and pregnant women. The latter can pose a risk to two humans, namely the mother herself and the fetus she is carrying. Therefore, the vaccination program for pregnant women at risk must be implemented immediately. However, this program of course still faces obstacles so that research on the concerns of pregnant women in dealing with COVID-19 vaccination must be determined. This quantitative study used a correlation analytic design with a cross sectional study approach. It took place at the Dauh Puri Sub-Public Health Center, Denpasar. The sample was pregnant women in TM I and TM II and had not received the COVID-19 vaccine as many as 70 pregnant women. The sampling technique was non-probability sampling. Data were collected through a questionnaire. Data analysis used non-parametric analysis, namely Spearman Rho Correlation. The results show that there was a relationship between the level of knowledge and the readiness of pregnant women but there was no relationship between education and the number of pregnancies and the readiness. Therefore, the level of knowledge becomes the only factor that affects the readiness of COVID-19 vaccination in pregnant women.